Two new species of Photonectes with blue luminous tissue on body, and a re-examination of P. mirabilis (Teleostei: Stomiidae) - Prokofiev, Artem M.; Klepadlo, Cynthia (Zootaxa, 2019)
Two new species of the mesopelagic genus Photonectes are described from the Pacific Ocean. Both of them are characterized by the presence of blue luminous tissue on the body. Photonectes cyanogrammicus new species, is characterized by the unique shape of the mental barbel, expanded distally and lacking bulbs or appendages. It is presently known only from the holotype collected in the Solomon Sea. Photonectes sphaerolampas new species, is described from four specimens collected in the western and central Pacific. It can be easily distinguished from the other species by the presence of the large spherical bulb of the mental barbel with darkly pigmented terminal appendage, split at its tip into several short filaments. Photonectes mirabilis Parr, 1927 is re-described, based on four specimens from the Atlantic and Pacific Oceans; details of jaw dentition and arrangement of the luminous tissue for this species are specified. A key for identification of the species of Photonectes with blue luminous tissue on the body is provided.